Quorum Sensing as an Antivirulence Strategy in Control of Bacterial Infections - Alnadia Yusriya Hibatullah; Besse Khalidatunnisa; Christina Aryanti Pada Soa; Ditta Putri Kumalasari (Science Tech Group, 2026)
Quorum sensing (QS) is a bacterial cell-to-cell communication system that plays a central role in regulating virulence, biofilm formation, pathogen adaptation, and infection persistence. The global rise in antimicrobial resistance, driven by conventional antibiotic use, has spurred the development of alternative, non-lethal strategies, including antivirulence approaches. This review aims to examine quorum sensing as an antivirulence target and to evaluate the potential of quorum-sensing inhibition (QSI) to control bacterial infection. A narrative literature review was conducted using scientific publications from 2016 to 2026 retrieved from reputable databases. The review highlights that QS regulates multiple pathogenic determinants, including virulence factor production, secretion system control, biofilm development, colonization processes, and bacterial survival within host environments. QSI-based interventions can be achieved through inhibition of signal molecule synthesis, enzymatic degradation of autoinducers, and receptor competition. This strategy potentially reduces selective pressure that causes resistance since it does not directly affect bacterial viability. Beyond clinical applications in chronic and biofilm-associated infections, QSI also has promising prospects in food safety, environmental management, and medical technologies. However, challenges related to compound stability, in vivo effectiveness, and potential bacterial adaptation require further investigation before broader clinical implementation can be achieved.